2019
DOI: 10.5173/ceju.2019.1951
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopy: a population based study of clinical complications and possible risk factors for stone surgery

Abstract: IntroductionThe aim of this study was to describe the complications of ureteroscopy (URS) and to investigate whether performing URS outside normal working hours leads to increased risk for clinically significant complications.Material and methodsA cohort of 486 consecutive patients treated with URS, with a total of 567 sessions between 2009 and 2015 at Helsingborg/Ängelholm Hospital, Sweden, was analyzed. Outcome was complications within 14 days after URS treatment.ResultsWe found no increased risk of complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…On the other hand, Berardinelli et al in 377 RIRS observed 15.1% of adverse events, including 8.4% (n = 30) post-operative, which revealed even lower prevalence: grade I in 6.9% (n = 26), grade II in 0.5% (n = 2), grade III in 0.5% (n = 2) [41]. Similarly, a Swedish study of 486 mixed semirigid and flexible URS groups by Wagenius et al described: grade I in 12.0% (n = 68), grade II in 6.5% (n = 7), grade III in 1.9% (n = 11) and grade IV in 0.2% (n = 1), which are comparable to the incidence of adverse events in the sample being discussed [42].…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, Berardinelli et al in 377 RIRS observed 15.1% of adverse events, including 8.4% (n = 30) post-operative, which revealed even lower prevalence: grade I in 6.9% (n = 26), grade II in 0.5% (n = 2), grade III in 0.5% (n = 2) [41]. Similarly, a Swedish study of 486 mixed semirigid and flexible URS groups by Wagenius et al described: grade I in 12.0% (n = 68), grade II in 6.5% (n = 7), grade III in 1.9% (n = 11) and grade IV in 0.2% (n = 1), which are comparable to the incidence of adverse events in the sample being discussed [42].…”
Section: Discussionmentioning
confidence: 59%